Cortical Auditory Evoked Potentials in (Un)aided Normal-Hearing and Hearing-Impaired Adults - Van Dun, Bram; Kania, Anna; Dillon, Harvey (Seminars in Hearing, 2016)
Cortical auditory evoked potentials (CAEPs) are influenced by the characteristics of the stimulus, including level and hearing aid gain. Previous studies have measured CAEPs aided and unaided in individuals with normal hearing. There is a significant difference between providing amplification to a person with normal hearing and a person with hearing loss. This study investigated this difference and the effects of stimulus signal-to-noise ratio (SNR) and audibility on the CAEP amplitude in a population with hearing loss. Twelve normal-hearing participants and 12 participants with a hearing loss participated in this study. Three speech sounds—/m/, /g/, and /t/—were presented in the free field. Unaided stimuli were presented at 55, 65, and 75 dB sound pressure level (SPL) and aided stimuli at 55 dB SPL with three different gains in steps of 10 dB. CAEPs were recorded and their amplitudes analyzed. Stimulus SNRs and audibility were determined. No significant effect of stimulus level or hearing aid gain was found in normal hearers. Conversely, a significant effect was found in hearing-impaired individuals. Audibility of the signal, which in some cases is determined by the signal level relative to threshold and in other cases by the SNR, is the dominant factor explaining changes in CAEP amplitude. CAEPs can potentially be used to assess the effects of hearing aid gain in hearing-impaired users.
Keywords: Cortical auditory evoked potential; hearing-impaired; normal-hearing; hearing aid; signal-to-noise ratio; audibility